2009
DOI: 10.1172/jci38994
|View full text |Cite
|
Sign up to set email alerts
|

The inability to disrupt the immunological synapse between infected human T cells and APCs distinguishes HIV-1 from most other primate lentiviruses

Abstract: Viruses that infect T cells, including

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
57
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 67 publications
(114 reference statements)
3
57
1
Order By: Relevance
“…25,27,28,30 Erk signaling is also targeted by Nef via an independent mechanism involving the NAKC complex that elevates HIV-1 transcription and exosome release. 48 Conceivably, the induction of TGN-associated Lck-Ras-Erk signaling represents a prerequisite for these subsequent functional Nef-Erk interactions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…25,27,28,30 Erk signaling is also targeted by Nef via an independent mechanism involving the NAKC complex that elevates HIV-1 transcription and exosome release. 48 Conceivably, the induction of TGN-associated Lck-Ras-Erk signaling represents a prerequisite for these subsequent functional Nef-Erk interactions.…”
Section: Discussionmentioning
confidence: 99%
“…11,30 In sharp contradiction to such elevated T-cell activation, Nef severely impairs the formation and organization of IS structures between Nef-expressing T lymphocytes and APCs by reducing the frequency of IS formation, blocking F-actin polarization at cell-cell contacts, and inducing mislocalization of the TCR itself and its effector kinase, Lck. 23,[30][31][32][33][34] These morphological alterations at the IS were accompanied by interference with early TCR signaling, such as induction of tyrosine phosphorylation. [32][33][34] How HIV-1 Nef induces this paradox scenario of enhanced downstream TCR signaling on disruption of signal initiation is unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, HIV-1 Nef severely impairs the formation and organization of IS structures between Nef-expressing T lymphocytes and APCs by reducing the frequency of IS formation, blocking Factin polarization at cell-cell contacts, and inducing mislocalization of the TCR itself as well as its effector kinase Lck (28,(35)(36)(37)(38)(39). These morphological alterations at the IS were accompanied by interference with early TCR signaling such as induction of tyrosine phosphorylation (36,37,39).…”
mentioning
confidence: 99%
“…HIV also modulates the expression of MHC class I and II [64,110], resulting in impaired CD8+ and CD4+ T cells response, respectively. It is also demonstrated that the immunological synapse between T cells and HIV infected mφ are not disrupted [111]; though, there is significant reduction in the expression of MHC and co-stimulatory molecules (CD80/86) [110,112]. Mycobacterium tuberculosis bacilli inhibit the fusion of phagosome and lysosome, and survives in the mφ.…”
Section: Macrophagesmentioning
confidence: 99%